PENGEMBANGAN MEDIA SISTEM PENCERNAAN PADA MANUSIA MENGGUNAKAN BAHAN BEKAS DI KELAS XI SMA NEGERI 2 GOWA - Nurindah Nurindah; Ahmad Afiif; Syahriani Syahriani; Syamsul Syamsul (BIOEDUKASI (Jurnal Pendidikan Biologi), 2022)
The lack of media and low interest in learning due to the use of printed books, the researchers carried out research to develop digestive system media in humans use used materials in class XI SMA Negeri 2 Gowa, to determine the level of validity of digestive system media in humans using used materials in class XI SMA Negeri 2 Gowa, to find out the practicality of the digestive system media in humans using used materials in class XI of SMA Negeri 2 Gowa. The research method is research and development (R & D), the results of the study show that the digestive system in humans using materials developed has a level of validity by a team of experts, namely 3.69, and the level of practicality by student responses and educator responses is in the practical category with an average value a total of 2.8. So that the learning media for the digestive system in humans uses materials that are suitable for use because they meet the criteria, are valid, and are practical.Kata kunci: bahan bekas, media pembelajaran, pengembangan